1988
DOI: 10.1172/jci113527
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the in vitro candidacidal activity of human neutrophil defensins by target cell metabolism and divalent cations.

Abstract: We tested the in vitro susceptibility of Candida albicans to three defensins from human neutrophilic granulocytes (HNP-1, 2, and 3), a homologous defensin from rabbit leukocytes (NP-1), and four unrelated cationic peptides. Although the primary amino acid sequences of HNP-1, 2, and 3 are identical except for a single amino-terminal amino acid alteration, HNP-1 and HNP-2 killed C. albicans but HNP-3 did not. C. albicans blastoconidia were protected from HNP-I when incubations were performed in the absence of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 33 publications
9
149
1
2
Order By: Relevance
“…The Candida albicans strains were insensitive to HNP3, which has a negatively charged Asp residue at this position. The results are consistent with the previously reported candidacidal activity of human defensins [28], although the C. albicans strains and the assay procedures used were different.…”
Section: Candidacidal Activitysupporting
confidence: 91%
See 2 more Smart Citations
“…The Candida albicans strains were insensitive to HNP3, which has a negatively charged Asp residue at this position. The results are consistent with the previously reported candidacidal activity of human defensins [28], although the C. albicans strains and the assay procedures used were different.…”
Section: Candidacidal Activitysupporting
confidence: 91%
“…There are variations in the sequences at the N-and C-termini and in the middle portion of these peptides. These differences have been found to be reflected in their antimicrobial spectrum and specificity of organisms for which they are cidal [14,28]. This functional diversity observed for similarly structured molecules raises interest in identifying the crucial residues responsible for their specificity and antimicrobial potency.…”
Section: Molecular Structure and Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies on human defensins (HNP1, -2, and -3)-mediated cytotoxicity showed the requirement for peptide internalization and for target cell metabolic processes (27). Other examples are the candidacidal activity of HNP-1, which is negatively affected in the presence of respiratory inhibitors (28), and the activity of killer toxin from Pichia kluyveri against Saccharomyces cerevisiae cells that is highly dependent on the physiological state of cells (29) in a very similar fashion as that described for histatin 5. It is therefore feasible that the present discovery that ROS formation is a quintessential step in the killing process provoked by histatin 5 is not restricted to histatin 5 activity, but may represent a common mechanism of target-cell killing afforded by agents that are dependent on active cell metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…As immune modulators, HNP-1, -2, and -3 upregulate TNF-α and interleukin (IL)-1 in human monocytes that have been activated by bacteria (61,62). Furthermore, HNP-1 and -2 have the ability to directly kill gram-negative and -positive bacteria (48), Candida albicans (63), and enveloped viruses such as members of the herpes family (64,65). HNP-5 has concentrationdependent microbicidal activity against Escherichia coli, Listeria monocytogenes, Salmonella typhimurium, and C. albicans (66).…”
Section: Host Defense (Antimicrobial) Peptidesmentioning
confidence: 99%